Evaluation of The Implementation of Merdeka Curriculum in Economics Learning at Senior High Schools in Yogyakarta City - Praseyo, Yohanes Bosco Adi; Muhson, Ali; Mwakapemba, James Leonard (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to evaluate the implementation of the independent curriculum implementation in senior high school economics learning which includes the components: (1) antecendents, (2) transactions, and (3) outcomes. This research used a quantitative approach with the Countenance Stake evaluation model. The subjects of this study consisted of 143 students and 4 public high school economics teachers in Yogyakarta City. Data collection was carried out using questionnaires, document reviews, and observations that were validated using Aiken content validity and Exploratory Factor Analysis construct validity. Reliability estimation of this study used Cronbach Alpha formula. The data analysis technique used quantitative descriptive analysis. The results of this study indicated that in the aspect of preparation (antecendents) of economic learning in the category of very good by obtaining an average score of 90%, which includes the characteristics of learning planning documents, the completeness of the contents of learning documents, preliminary learning steps, and learning strategies. In the aspect of implementation (transaction) of economic learning in the very good category by obtaining an average score of 88.07%, which includes learning that was interactive, inspiring, fun, challenging, motivating, providing initiative and creativity, and providing role models, mentoring and facilitation. In the aspect of economic learning outcomes in the good category by obtaining an average score of 73.59%, which includes skills assessment, knowledge assessment of daily tests, mid-semester summative, end-of-semester summative, and assessment of student attitudes.